Professional Development for the Experienced Music Educator: A Review of Recent Literature. (June 2019) - Koner, Karen; Eros, John
There is a rich body of literature on professional development in music education, including research that has examined the professional development needs of experienced music teachers specifically. In fact, music teachers' professional development needs may be affected by their degree of experience in the profession. The purpose of this literature review is to examine scholarship during the period 2007 to 2017 about the professional development needs of experienced K–12 music educators. Initial examination of literature in this area shows two emerging themes, including changing needs throughout the career and informal interactions among music educators, being highly effective.